Targeting the Integrated Stress Response in Cancer Therapy - Tian, Xiaobing; Zhang, Shengliang; Zhou, Lanlan; Seyhan, Attila A.; Hernandez Borrero, Liz; Zhang, Yiqun; El-Deiry, Wafik S. (Frontiers in Pharmacology, 2021)
The integrated stress response (ISR) is an evolutionarily conserved intra-cellular signaling network which is activated in response to intrinsic and extrinsic stresses. Various stresses are sensed by four specialized kinases, PKR-like ER kinase (PERK), general control non-derepressible 2 (GCN2), double-stranded RNA-dependent protein kinase (PKR) and heme-regulated eIF2α kinase (HRI) that converge on phosphorylation of serine 51 of eIF2α. eIF2α phosphorylation causes a global reduction of protein synthesis and triggers the translation of specific mRNAs, including activating transcription factor 4 (ATF4). Although the ISR promotes cell survival and homeostasis, when stress is severe or prolonged the ISR signaling will shift to regulate cellular apoptosis. We review the ISR signaling pathway, regulation and importance in cancer therapy.